Description Of Students' Mathematical Problem-Solving Ability In The Topic Of Setting Up Equations In The Cambridge Curriculum - Erdita Aulia Syaharani; Arief Agoestanto; Tri Sri Noor Asih (Green Publisher Indonesia, 2024)
Mathematical problem-solving is a crucial ability that needs to be developed to prepare students to face the challenges of the 21st century. The aim of this research is to describe the mathematical problem-solving abilities of high school students in the Setting Up Equations topic within the Cambridge Curriculum schools. This research used descriptive qualitative approach. The sample for this research was taken using purposive sampling technique, consisting of 23 students from the 10th grade of Semesta Bilingual School Semarang. Data were obtained through test technique, then scoring was conducted to gather percentages at each stage, followed by an averaging process for the final interpretation of students’ mathematical problem-solving abilities. The instrument used has been well validated and consists of 5 contextual questions in the form of essay questions. The results obtained were that 74% of students understand the problem, 67% can devise a plan, 78% can carry out the plan, and 4% can look back. The average final percentage of students’ abilities was 56%, categorized as medium. It is concluded that students’ mathematical problem-solving abilities are still considered medium, indicating the need for improvement efforts.